Measuring Trust In Romantic Relationships: Validation Of The Trust In Close Relationship Scale In Indonesian - Claresta, Felicia; Djaja, Ngadiman (UNIVERSITAS PAKUAN, 2025)
Trust is an important foundation in a healthy and sustainable romantic relationship. This study aims to test the psychometric properties of the Indonesian version of the Trust in Close Relationship Scale adapted from Rempel, Holmes, and Zanna (1985). A total of 416 respondents (208 heterosexual couples) aged 18–65 years were recruited through a purposive sampling technique. The instrument consists of 26 items measuring three dimensions of trust: faith, dependability, and predictability. The validation procedure includes content validity testing using Aiken's V, readability testing, and construct validity through Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). Convergent validity was tested using the Dyadic Adjustment Scale (DAS-32) and discriminant validity with the Ten Item Personality Inventory (TIPI). The EFA results showed a three-factor structure, but two factors included items across the original dimensions, which were later renamed to Belief, Predictability, and Reliability. CFA on 16 selected items showed adequate model fit (CFI=0.939; TLI=0.928; RMSEA=0.0683). Convergent validity showed that Reliability and Predictability were positively correlated with relationship quality (DAS-32), while Confidence showed a negative correlation. Discriminant validity showed a weak relationship between trust dimensions and personality (TIPI). Reliability tests showed high internal consistency (α=0.720–0.921). This study concluded that the Indonesian version of the Trust Scale is valid and reliable for measuring trust in romantic relationships, although differences in factor structure were found that were influenced by local cultural contexts